Implementasi Metode A*Star Pada Pencarian Rute Terdekat Menuju Tempat Kuliner di Menes Pandeglang Banten - Robby Rizky; Taufik Hidayat; Asep Hardiyanto Nugroho; Zaenal Hakim (Program Studi Pendidikan Geografi Universitas Hamzanwadi, 2020)
Menes is one of the districts in Pandeglang Regency, Banten Province which has many culinary place as tourist destinations. Most of the tourists visiting come from outside the Pandeglang Regency area and even outside Banten Province. To reach culinary place in Menes District, tourists often get lost or pass quite a long distance due to the many routes that can be traversed to the culinary place. Therefore, this study aims to find the nearest route to culinary place in the District of Menes, Pandeglang Regency. The method used in this study is the A * Star method. This method is believed to be very accurate to solve the problem because it has heuristic calculations that are able to count the existing nodes. The data used for this research is data from Google Maps. After the image is obtained, the data will be converted into a grid which then becomes a benchmark calculation. Based on the results of the study it can be concluded that the use of the A * Star method can be used to find the nearest route to culinary place in the District of Menes Pandeglang Regency, via Serang-Palima-Ciomas-Menes route with a distance of 45,987 km.